Pemanfaatan Ekstrak Gulma Kirinyuh (Chromolaena odorata L.) sebagai Bioherbisida untuk Pengendalian Gulma di Kelapa Sawit (Elaeis guineensis Jacq.) - Buel Arjodi Harianja; Makhrani Sari Ginting (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Weed management represents a critical determinant in oil palm (Elaeis guineensis Jacq.) productivity, as weed competition for essential resources significantly reduces yield. The ecological risks associated with synthetic herbicide dependency necessitate the development of plant-based bioherbicides. This study investigated the efficacy of Chromolaena odorata L. extracts derived from different plant organs at varying concentrations in controlling weed populations. A factorial Randomized Complete Block Design (RCBD) was employed, evaluating two factors: plant parts (leaves, stems, and roots) and extract concentrations (0%, 10%, 20%, and 30%). Parameters including phytotoxicity intensity, mortality rate, and regrowth period were analyzed. Results indicated a significant interaction between the variables, where a 30% leaf extract concentration achieved the highest phytotoxicity (73.50%), the most rapid mortality (4.33 days), and the longest regrowth suppression (20.67 days). These findings confirm that the leaf-derived allelochemicals of C. odorata provide a potent and sustainable alternative for integrated weed management in oil palm ecosystems.